Work–Life Balance and Diversity Management: A New Approach to Old Problems - Parisse, Chiara Alberta (Social sciences (Basel), 2025)
This study aims to address the sociological and legal evolution of the work–life balance theme and the concept of the valorisation of differences through a diversity management approach in order to create a culture of gender equality and inclusion in the workplace. The analysis is conducted through a comparative methodology, as legislative sources are analysed in the supranational, European, and Italian contexts while identifying differences in diversity management in the US and Europe. Moreover, with a case-study methodology, innovative strategies put in place by an Italian and an American company are identified, demonstrating how diversity management can contribute to a better work–life balance and gender equity. The ultimate, innovative aim is to highlight that differences and an orientation toward diversity management can ensure that management practices recognise the transversality and complexity of individuals and provide equal opportunity to subjects in all categories.